1993
DOI: 10.1002/cne.903370111
|View full text |Cite
|
Sign up to set email alerts
|

Calcium dependence of differentiation of GABA immunoreactivity in spinal neurons

Abstract: The developmental regulation of neurotransmitter synthesis has been extensively studied and appears in many cases to depend on electrical activity. The central nervous system of the Xenopus embryo and young larva is an attractive subject for such studies, since action potentials first elicited from Xenopus spinal neurons at the time of closure of the neural tube are long in duration and calcium-dependent. Moreover, cells exhibit spontaneous elevations of intracellular calcium during this early period as a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 58 publications
0
35
0
Order By: Relevance
“…These early effects are briefly summarized here as they provide an excellent illustration of the multiple facets of the actions of GABA and the unique role of GABA as an early communicating signal. Excellent reviews of these effects have been published (36,352,492,579).…”
Section: Early Operation Of Gaba a Signaling Prior To Synapse Formentioning
confidence: 99%
“…These early effects are briefly summarized here as they provide an excellent illustration of the multiple facets of the actions of GABA and the unique role of GABA as an early communicating signal. Excellent reviews of these effects have been published (36,352,492,579).…”
Section: Early Operation Of Gaba a Signaling Prior To Synapse Formentioning
confidence: 99%
“…When spikes and waves are eliminated in 0 Ca 2ϩ medium, the normal speeding of delayed K ϩ current activation does not occur, fewer neurons develop the GABA phenotype (quantified by both GABA immunoreactivity and GAD transcripts), and neurites are abnormally long (145, 248,249,557,607).…”
Section: Developmental Rolesmentioning
confidence: 99%
“…Xenopus spinal neurons cultured from neurula stage embryos exhibit spontaneous, transient elevations of intracellular calcium ([Ca 2ϩ ] i ) before and after neurite initiation that are required for appropriate expression of the neurotransmitter GABA and maturation of K ϩ current kinetics (Holliday and Spitzer, 1990;Desarmenien and Spitzer, 1991;Spitzer et al, 1993;Gu and Spitzer, 1995). By the earliest time of neurite initiation, primary spinal neurons display Ca 2ϩ -dependent action potentials and mature Ca 2ϩ current density (Spitzer and Lamborghini, 1976;Barish, 1986;O'Dowd et al, 1988;Spitzer, 1991), implying that voltagedependent currents appear at an earlier stage.…”
Section: Abstract: Xenopus Spinal Neurons; Circus Movements; Lobopodmentioning
confidence: 99%
“…Previous work demonstrated that Ca 2ϩ influx through voltagedependent Ca 2ϩ channels regulates aspects of spinal neuron differentiation (Desarmenien and Spitzer, 1991;Spitzer et al, 1993;Gu and Spitzer, 1995). Because voltage-clamped Ca 2ϩ currents in circus cells were typically small, Ca 2ϩ imaging was used to determine whether they are sufficient to produce detectable elevations of [Ca 2ϩ ] i in response to depolarization and to confirm the developmental profile of expression of Ca 2ϩ currents during the first 6 hr in culture.…”
Section: Calcium Elevations In Response To Depolarization With Kclmentioning
confidence: 99%